The Idioptera-Eloeophila complex (Diptera: Limoniidae): a phylogenetic solution to an old taxonomic misunderstanding - Daubian Santos; Guilherme Cunha Ribeiro (Arthropod Systematics & Phylogeny, 2024)
Abstract Eloeophila Rondani, 1856 and Idioptera Macquart, 1834 are two genera of the family Limoniidae (Diptera) distinguished by the presence of a supernumerary cross-vein m-cu. Although these genera were previously combined, there has been a lack of phylogenetic tests to investigate the evolutionary relationship between them. In this study, we conducted a cladistic analysis that indicates that Idioptera form a clade within Eloeophila, and therefore the two genera should be synonymized under Idioptera. Consequently, 87 species of Eloeophila are transferred to Idioptera.